Export performance and market retention of turmeric oleoresin from India: A Markov chain approach - Mugilan, G; Divya, K; Malarkodi, M; Kavitha, M; Ashok kumar, G (Plant Science Today, 2025)
Turmeric oleoresin is a valuable extract from Curcuma longa. it plays a vital role in the food, pharmaceutical and nutraceutical sectors. India is the greatest producer in the world and contributes significantly to turmeric oleoresin exports. This study uses Markov Chain analysis and the Compound Annual Growth Rate (CAGR) to evaluate India's export performance from 2003 to 2024. Following 2014, the Mission for Integrated Development of Horticulture saw a policy-driven boom that led to a CAGR of 16.06 %. The Markov Chain study, based on export quantity data from 2018 to 2024, simulates the direction of trade and reveals country-level market retention and share transitions. High market loyalty was noted in nations like the USA (83 %), Germany (83 %), France (85 %) and the UK (80 %), whereas emerging or volatile markets such as China (60 %), the UAE (60 %) and the “Others” group, which accounted for 50 %, exhibited lower retention and more volatility. To identify reoccurring problems like pesticide residues, microbiological contamination, unauthorised additions and labelling errors, the study also integrates trade rejection data from the EU's Rapid Alert System for Food and Feed (RASFF) and weekly alerts from the Indian trade portal. These rejections cause export volatility in emerging markets and have immediate economic effects. According to the findings, India's export competitiveness and sustainability will be enhanced by combining high-retention markets and reducing rejection risks through improved traceability, chemical residue monitoring and regulatory compliance.